2023
DOI: 10.3390/jmse11010074
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and Biogeography of Coral Mucus-Associated Bacterial Communities: The Case of Acropora formosa

Abstract: The role of microorganisms in coral health, disease, and nutrition has been demonstrated in various studies. Environmental factors including pH, temperature, and dissolved oxygen also play crucial roles in maintaining sustainable coral ecosystems. However, how geographical and environmental factors influence bacterial diversity and community composition is unclear. Here, bacterial communities associated with Acropora formosa coral were sampled from four different locations—Phu Quoc Islands (Vietnam), Nha Trang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 40 publications
0
0
0
Order By: Relevance
“…Moreover, it has been observed that bacterial communities undergo changes corresponding to the health status of corals [17]. Research has demonstrated that bacterial communities can enhance coral's resistance and aid it in coping with coral bleaching events [7,18].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it has been observed that bacterial communities undergo changes corresponding to the health status of corals [17]. Research has demonstrated that bacterial communities can enhance coral's resistance and aid it in coping with coral bleaching events [7,18].…”
Section: Introductionmentioning
confidence: 99%